P47 Extent of paediatric exposure to pharmaceutical excipients: an exploratory study. Issue 9 (19th August 2020) - AbouDaya, Mohammed; Tomlin, Stephen; Rashed, Asia N
Abstract : Aim: The assumption that excipients are inactive therefore non-harmful to patients is a declining opinion due to raised safety concerns of excipient activity, particularly in children. 1 There is limited data on the safety of excipients in children and a lack of standardisation of the risk-benefit use of excipients in the different paediatric populations. 2 This study aimed to investigate the extent of excipient exposure in children taking long-term oral liquids, admitted to Hospital, and to identify whether patients could be switched to a solid alternative due to the harm posed from liquid formulations. Method: A prospective observational study conducted in a UK paediatric hospital. The electronic medication chart for hospitalised children aged 0–18 years on long-term (for ≥6 weeks) oral liquid medicines, were reviewed over a four-week period. A priority list of eight excipients (called harmful excipients) with known reported hazards was developed based on literature: propylene glycol, ethanol, parabens, benzyl alcohol, aspartame, sorbitol, polysorbate 80 and benzoic acid. The list was used to determine the extent of children exposure to the harmful excipients. Considering patient factors (age, swallowing ability, treated condition), prescribed dose and availability of solid dosage forms, the included long-term liquid medicines were assessed for a potential solid form alternative by a specialist paediatric clinical pharmacist. Results: A total of 302 oral liquid medicine formulations prescribed for 60 patients (age range 10 days – 17 years) were included in the study, of which 68.9% (208/302) were long-term oral liquid formulations. The 208 oral liquid formulation contained a total of 1044 excipients resulted in 17.4 (± 9) excipients per patients. Majority of patients (98.3%, 59/60) were exposed to at least one harmful excipient in their medicines. Children aged 2–11 years and 6–11 years were exposed the most to harmful excipients (mean 8.2 ± 4.9 exposure per patient). Parabens (81.7%, 49/60) was the most common harmful excipient patients were exposed to, followed by sorbitol (76.7%, 46/60), ethanol (75.0%, 45/60) and propylene glycol (70.0%, 42/60). Considering patient factors, prescribed dose and availability of solid formulations, it was found that almost third of the prescribed long-term oral liquid medicines (33.0%, 68/208) could be switched to tablet or capsule forms by pharmacist without any change to the prescribed dose. While for another 3.4% (7/208) long-term liquid medicines could be switched to solid dosage forms with prescriber approval, as prescribed doses would need to be adjusted slightly. Conclusion: The study highlights the extent of excipients exposure in children on long-term oral liquid medicines, many of which could potentially be harmful. Healthcare professionals should aim to reduce the long-term risks of excipients by providing an oral solid substitute to replace oral liquid formulation, where possible, and ensuring excipients are within safe, acceptable limits. References: Fabiano V, Mameli C, Zuccotti GV. Paediatric pharmacology: remember the excipients. Pharmacol Res 2011;63 :362–365. Buckley L, Salunke S, Thompson K, et al . Challenges and strategies to facilitate formulation development of pediatric drug products: Safety qualification of excipients. Int J Pharm 2018; 536:563–569.